(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Areas of social systems - regions and their development is the key for national development, main vector of prosperity growth. There can be no prosperity without a strong and developed the country's regions.0 The article dealt with regionics- science that subject of studies are relatively small regions at NUTS-3 level with its historically established determinate territory, the cultural and ethnic identity, their development problems in the environmental dimension aspect. There is analyzed one of the most identical Latvian region - Latgale.